2021
DOI: 10.1097/bot.0000000000001978
|View full text |Cite
|
Sign up to set email alerts
|

Reverse or Hemi Shoulder Arthroplasty in Proximal Humerus Fractures: A Single-Blinded Prospective Multicenter Randomized Clinical Trial

Abstract: Objectives: To compare outcomes between hemiarthroplasty (HA) and reversed shoulder arthroplasty (RSA) as a treatment for dislocated 3-part and 4-part proximal humerus fractures in the elderly population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 55 publications
0
16
0
1
Order By: Relevance
“…At 12 months, the RTSA group demonstrated greater forward flexion and a greater Constant score. However, there were no differences in terms of external or internal rotation or VAS, DASH, or SF-12 (12-Item Short Form Health Survey) scores 56 .…”
Section: Critical Analysis Review Of Rtsa In Comparison With Other Tr...mentioning
confidence: 78%
“…At 12 months, the RTSA group demonstrated greater forward flexion and a greater Constant score. However, there were no differences in terms of external or internal rotation or VAS, DASH, or SF-12 (12-Item Short Form Health Survey) scores 56 .…”
Section: Critical Analysis Review Of Rtsa In Comparison With Other Tr...mentioning
confidence: 78%
“…We found that surgeons are increasingly treating PHFs in the elderly with RSA instead of HA or ORIF, which is generally corroborated by recent literature. 18,24 We also identified differences based on fellowship training; shoulder surgeons more commonly recommended arthroplasty in tuberosity comminution and significant metaphyseal comminution, whereas trauma surgeons preferred ORIF or nonoperative management.…”
Section: Discussionmentioning
confidence: 99%
“…In the aforementioned metaanalysis, 35 only 28% of 4-part fractures were treated with ORIF; HA was more common (56%). 35 Most studies demonstrate superior outcomes in 3-and 4-part PHFs treated with RSA compared with HA 6,8,15,24 and ORIF, 6 but superiority to nonoperative management has yet to be shown. 27,37 Although 2-part fractures are typically well managed with ORIF or nonoperative management, the best surgical treatment for 3-and 4-part fractures may depend on other factors besides fracture morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no differences between the two groups with respect to WOOS index score, EQ-5D index score, and tuberosity healing. Another recent RCT [ 44 ] comparing RTSA to HA for acute PHF ( n = 33) in patients greater than 65 years demonstrated improved DASH score and range of motion (forward flexion and abduction) with RTSA. There are multiple non-randomized prospective and retrospective studies [ 35 , 41 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] comparing RTSA and HA in the treatment of PHF ( Table 3 ).…”
Section: Evidence For the Use Of Rtsa In Phf Compared To Other Surgic...mentioning
confidence: 99%